2006
DOI: 10.1136/jcp.2006.038356
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and quantitative mRNA assessment of ghrelin expression in gastric and oesophageal adenocarcinoma

Abstract: Background: Ghrelin is an orexigenic gut peptide produced predominantly by the stomach. Gastric mucosal ghrelin production could be compromised by an infiltrating adenocarcinoma. Aims: To assess the expression of ghrelin mRNA and peptide in oesophagogastric adenocarcinomas and adjacent non-neoplastic mucosa. Methods: 10 gastric and 22 oesophageal adenocarcinoma archival samples were randomly selected from a database. The presence of ghrelin-positive cells was assessed in cancer and corresponding non-neoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Interestingly, several studies revealed that ghrelin expression in cancer cells is decreased in comparison to healthy tissue. This was observed in thyroid, stomach, esophagus, pancreas and renal cell carcinoma [28,[34][35][36]. Therefore, if pro-proliferative properties of ghrelin should be considered, it could be discussed if its absence or poor expression in cancer tissue provides protection from further growth.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies revealed that ghrelin expression in cancer cells is decreased in comparison to healthy tissue. This was observed in thyroid, stomach, esophagus, pancreas and renal cell carcinoma [28,[34][35][36]. Therefore, if pro-proliferative properties of ghrelin should be considered, it could be discussed if its absence or poor expression in cancer tissue provides protection from further growth.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that ghrelin may enhance the proliferation of prostate and pancreatic (Duxbury et al, 2003) cancer cells, but not of a lung cancer cell line, where it induced dose-dependent inhibition of cell proliferation and increased apoptosis (Cassoni et al, 2006). Some tumours from archival samples express ghrelin , whereas others do not (Cassoni et al, 2006;Mottershead et al, 2007). Tumour incidence is not increased in patients with anorexia nervosa (Mellemkjaer et al, 2001) despite elevated ghrelin levels.…”
Section: Intravenous Ghrelin For Cancer Anorexia/cachexia F Strasser mentioning
confidence: 99%
“…In vitro studies suggest that ghrelin may enhance the proliferation of prostate [50] and pancreatic [51] cancer cells, but not of a lung cancer cell line, where it induced dose-dependent inhibition of cell proliferation and increased apoptosis [52]. Some tumors from archival samples express ghrelin [53], whereas others (gastric cancer and esophageal cancer) do not [54]. According to a review that analyzed ghrelin administration studies, there was no report of anyone suffering from new cancer as an adverse event among 1,850 participants who were registered to 121 studies.…”
Section: Effects Of Ghrelin Administration After Total Gastrectomymentioning
confidence: 99%